Chronic Kidney Disease Awareness Campaign and Mobile Health Education to Improve Knowledge, Quality of Life, and Motivation for a Healthy Lifestyle Among Patients With Chronic Kidney Disease in Bangladesh: Randomized Controlled Trial - Mohammad Habibur Rahman Sarker; Michiko Moriyama; Harun Ur Rashid; Md Moshiur Rahman; Mohammod Jobayer Chisti; Sumon Kumar Das; Samir Kumar Saha; Shams El Arifeen; Tahmeed Ahmed; A S G Faruque (JMIR Publications, 2022)
BackgroundChronic kidney disease (CKD) is linked to major health consequences and a poor quality of life. Despite the fact that CKD is becoming more prevalent, public knowledge of the disease remains low. ObjectiveThis study aimed to evaluate the outcome of a health education intervention designed to enhance knowledge, health-related quality of life (QOL), and motivation about healthy lifestyle among adults with CKD. MethodsThis study was a parallel-group (1:1), randomized controlled trial in the Mirzapur subdistrict of Bangladesh that compared 2 groups of patients with CKD. Adults with CKD (stages 1-3) were enrolled in November 2020 and randomly assigned the intervention or control group. The intervention group received health education through a CKD awareness campaign and mobile health technologies and was observed for 6 months, whereas the control group received standard treatment. The primary outcome was the evaluation of improved scores on the CKD knowledge questionnaire, and the secondary outcomes were improved QOL and changes in the levels of blood pressure (BP), BMI, serum creatinine, fasting blood sugar (FBS), hemoglobin, cholesterol, high-density lipoprotein cholesterol, triglyceride, serum uric acid, blood urea nitrogen (BUN), and albumin-to-creatinine ratio. ResultsThe study enrolled 126 patients (control: n=63; intervention: n=63) and performed intention-to-treat analysis. The analyses included repeated measures ANOVA, and the results were observed to be significantly different from within groups (P<.001), between groups (P<.001), and the interaction of group × time factor (P<.001) for knowledge score. Diastolic BP and BMI showed significant differences arising from within groups (P<.001 and P=.01, respectively) and the interaction of group × time factor (P=.001 and P=.02, respectively); food salinity and hip circumferences showed significant differences arising from within groups (P=.001 and P=.03, respectively) and between groups (P=.001 and P=.02, respectively). Moreover, systolic BP and waist circumference showed significant differences from within groups (P<.001 and P=.003, respectively). However, no significant differences were found arising from within groups, between groups, and the interactions of group × time for QOL, urine salinity, and mid-upper arm circumference. Regarding the laboratory findings, from baseline to 6 months, the mean (SD) FBS decreased by 0.51 (3.77) mmol/L in the intervention group and 0.10 (1.44) mmol/L in the control group (P=.03); however, blood urea nitrogen increased by 3.64 (7.17) mg/dL in the intervention group and 1.68 (10.10) mg/dL in the control group (P=.01). ConclusionsThe health education strategy, which included a campaign and mobile health, showed promise for enhancing CKD knowledge among patients with CKD. This strategy may also aid patients with CKD in controlling their FBS and BP. The combined health education initiatives give evidence for scaling them up in Bangladesh and possibly other low- and middle-income countries, particularly in rural and peri-urban settings. Trial RegistrationClinicalTrials.gov NCT04094831; https://clinicaltrials.gov/ct2/show/NCT04094831. International Registered Report Identifier (IRRID)RR2-10.2196/30191